A new stem nematode associated with peanut pod rot in China: morphological and molecular characterization of Ditylenchus arachis n. sp. (Nematoda: Anguinidae). (16th January 2014) - Zhang, S. L.; Liu, G. K.; Janssen, T.; Zhang, S. S.; Xiao, S.; Li, S. T.; Couvreur, M.; Bert, W.
<x xml:space="preserve">Abstract</x> Surveys conducted in peanut production areas of China revealed peanut pod rot in several fields in Shandong and Hebei Provinces, China. A large quantity of an unknown stem nematode was isolated from the hulls and seeds of peanuts, herein described as Ditylenchus arachis n. sp. The new species is characterized by a combination of the following features: lateral lip sectors distinctly projected, stylet delicate, 8·4–10 μm in length, six lines in the lateral field, tail elongate–conoid, bursa covering about 68–86% of tail length. Pathogenicity tests showed that D. arachis n. sp. could infect peanut (Arachis hypogaea), but not sweet potato (Ipomoea batatas) or potato (Solanum tuberosum). Morphologically, D. arachis n. sp. appears closest to D. africanus, D. myceliophagus and D. destructor, but can be differentiated based upon a combination of morphological characteristics, host preference and molecular sequence data. The results of the phylogenetic analysis, based on 18S rDNA, the D2–D3 expansion region of 28S rDNA, and the ITS1–5·8S–ITS2 region, confirmed its status as a new species. A sister relationship with D. destructor was appointed, rather than with its ecologically very similar congener D. africanus.